The Positive Effect And Importance Of Innovative Technologies On The Educational System - Jonikulova Durdona (Journal of Learning on History and Social Sciences, 2024)
This article presents concepts about innovative technologies in education and the main basis of pedagogical technology - the importance and useful aspects of selected technologies for the teacher and student to achieve a guaranteed result from the set goal.